Will E-Monitoring of Policy and Program Implementation Stifle or Enhance Practice? How Would We Know? - Kathleen P. Conte; Kathleen P. Conte; Penelope Hawe; Penelope Hawe; Penelope Hawe (Frontiers Media S.A., 2018)
Electronic or digital monitoring systems could promote the visibility of health promotion and disease prevention programs by providing new tools to support the collection, analysis, and reporting of data. In clinical settings however, the benefits of e-monitoring of service delivery remain contested. While there are some examples of e-monitoring systems improving patient outcomes, the smooth introduction into clinical practice has not occurred. Expected efficiencies have not been realized. The restructuring of team work has been problematic. Most particularly, knowledge from research has not advanced sufficiently because the meaning of e-monitoring has not been well theorized in the first place. As enthusiasm for e-monitoring in health promotion grows, it behooves us to ensure that health promotion practice learns from these insights. We outline the history of program monitoring in health promotion and the development of large-scale e-monitoring systems to track policy and program delivery. We interrogate how these technologies can be understood, noticing how they inevitably elevate some parts of practice over others. We suggest that progress in e-monitoring research and development could benefit from the insights and methods of improvement science (the science that underpins how practitioners attempt to solve problems and promote quality) as conceptually distinct from implementation science (the science of getting particular evidence-based programs into practice). To fully appreciate whether e-monitoring of program implementation will act as an aid or barrier to health promotion practice we canvass a wide range of theoretical perspectives. We illustrate how different theories draw attention to different aspects of the role of e-monitoring, and its impact on practice.